Penerapan Asesmen Kinerja Melalui Pbm Untuk Meningkatkan Kemampuan Berpikir Kritis Dan Kreatif Matematik - Santoso, Erik (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2014)
The purpose of this study is to see improvement of critical and creative thinking mathematic skills among students are learning to use asasmen performance in problem-based learning, with students who are learning using problem-based learning and student learning using conventional learning. This includes quasi-experimental study with mixed methods through Concurrent Embedded strategies. The study was conducted in SMP 6 Tasikmalaya, the subject are three samples of class VII. Instruments used include test questions critical and creative thinking skills of mathematics. Quantitative data analysis using ANOVA test one and two lines, followed by Scheffe test. In the qualitative analysis carried out on the attitude scale, and assessment of performance, and the results of the interview. The results showed that 1 ) there are differences in improvement of critical thinking skills of students receiving mathematical application of performance assessment in problem-based learning, 2 ) there differences in improvement of creative thinking ability of students receiving mathematical application of performance assessment in problem-based learning, 3) there is a relationship between critical thinking skills with the ability creative thinking, 4) positive student attitudes after implementation of performance assessment in problem-based learning